A cancer of undetermined significance: Incidental thyroid carcinoma. Issue 5 (29th November 2018) - Evranos, Berna; Polat, Sefika Burcak; Cuhaci, Fatma Neslihan; Baser, Husniye; Topaloglu, Oya; Kilicarslan, Aydan; Kilic, Mehmet; Ersoy, Reyhan; Cakir, Bekir
Abstract : Introduction: The incidence of thyroid cancer is increasing which can be attributed in part to improved ultrasonography (US) methods and increased detection of incidental thyroid carcinomas (ITC). We aimed to compare ITC with nonincidental thyroid carcinomas (NITC) in this study. Methods: Retrospective analyses of 906 individual patients who were operated for benign and malignant thyroid disease and had a final histopathological diagnosis of thyroid carcinoma were enrolled in this study. Preoperative US examination and fine needle aspiration (FNA) biopsy results were evaluated. The tumor foci in thyroidectomy specimens that were not represented in preoperative US or FNA reports were classified as ITC. The tumor foci that match with the lesions defined in US or FNA results were classified as NITC. Results: Final histology revealed ITC in 326 patients (36%) and NITC in 580 patients (64% Mean age was 51.7 ± 11.11 in ITC group and 48.15 ± 13.1 in NITC group ( P < .001). In NITC group 322 (55.5%) of the patients were operated for suspicious cytology while only 29 (8.9%) of the patients in the ITC group were operated because of this indication ( P < .001). There were 1301 cancer foci in histopathology specimens. Among all these cancer foci, 434 (33.3%) were detected incidentally and 867 (66.7%) were detected non‐incidentally. About 779 (89.9%) of nonincidental cancer foci were papillary cancer (PTC), while all of the incidental cancer foci were PTC. Mean size was 13 mm in NITC group and it was 3 mm in the ITC group and differed significantly between the groups ( P < .001). Tumor size was ≤1 cm in 35.2% of the patients with NITC while 98.5% of patients with ITC had tumor ≤1 cm. The occurrence of multinodularity was higher in ITC than the NITC group ( P < 001). Median TSH level was higher in patients with NITC than ITC while both were in the reference range (1.53 vs 1.03 μIU/mL, P < .001). The frequency of thyroiditis detected by US, and thyroid peroxidase antibody and thyroglobulin antibody positivities were similar in patients with ITC and NITC ( P = .2, P = .86, and P = .26, respectively). The frequencies of capsular invasion (29.1% vs 7.9%), extrathyroidal extension (13% vs 4.2%), multifocality (35.8% vs 24.2%), non‐complete resection (9.2% vs 1.8%), and lymph node metastasis (9.5% vs 1.8%) were significantly higher in the NITC group ( P < .001, for each). Persistent/recurrent disease in patients with NITC was more frequent than patients with ITC ( P = .004). This outcome was similar for cancers measuring ≤1 cm ( P = .001). Conclusion: ITC is often encountered in older patients and frequently determined in early stages with more favorable histopathological features and better prognosis.